Prevalence and antimicrobial susceptibility pattern of methicillin resistant Staphylococcus aureus isolated from clinical samples at Yekatit 12 Hospital Medical College, Addis Ababa, Ethiopia - Dilnessa, Tebelay (BMC Infect Dis, 2016)
BACKGROUND: Staphylococcus aureus particularly MRSA strains are one of the major causes of community and hospital acquired bacterial infections. They are also becoming increasingly multi-drug resistant and have recently developed resistance to vancomycin, which has been used successfully to treat MRSA for many years. In-vitro determination of drug resistance patterns of S. aureus is critical for the selection of effective drugs for the treatment of staphylococci infections. The main aim of this study was to determine the prevalence of methicillin resistant S. aureus strains from different clinical specimens from patients referred for routine culture and sensitivity testing. METHOD: A cross sectional study was conducted among 1360 participants at Yekatit 12 Hospital Medical College in Ethiopia from September 2013 to April 2014. Clinical samples from various anatomical sites of study participants were cultured on blood agar and mannitol salt agar and identified to be S. aureus by using catalase, coagulase and DNAse tests. S. aureus isolates then were screened for MRSA using 30 μg cefoxitin disc and other 11 antimicrobial drugs by disc diffusion procedure, and agar dilution and E tests for vancomycin. All S. aureus isolates examined for beta-lactamase production by employing nitrocefin. Data were analyzed using SPSS version 20 software and logistic regressions were applied to assess any association between dependent and independent variables. RESULTS: Of 1360 clinical specimens analyzed S. aureus was recovered from (194, 14.3 %). Rate of isolation of S. aureus with regard to clinical specimens was the highest in pus (118, 55.4 %).No S. aureus was isolated from CSF and urethral discharge. Out of 194 S. aureus isolates, (34, 17.5 %) were found out to be MRSA and the remaining (160, 82.5 %) were MSSA. Ninety eight (50.5 %) S. aureus were multi drug resistant and the highest isolates were resistant to penicillin (187, 96.4 %) and least resistant for clindamycin (23, 11.9 %) and vancomycin (10, 5.1 %). MRSA strains were 100 % resistant to penicillin G, erythromycin, trimethoprim-sulfamethoxazole and least resistant to vancomycin (10, 29.4 %). Out of 194 S. aureus isolates (153, 79.0 %) were beta-lactamase producers. CONCLUSION: In this study S. aureus isolates exhibited very high degree of resistance to different antibiotics. The isolates were also multidrug resistant to several combinations of the tested antibiotics. The emergence of vancomycin resistant S. aureus highlights the value of prudent prescribing of antibiotics and avoiding their irrational use.